2010
DOI: 10.1073/pnas.1006442107
|View full text |Cite
|
Sign up to set email alerts
|

Proangiogenic scaffolds as functional templates for cardiac tissue engineering

Abstract: We demonstrate here a cardiac tissue-engineering strategy addressing multicellular organization, integration into host myocardium, and directional cues to reconstruct the functional architecture of heart muscle. Microtemplating is used to shape poly(2-hydroxyethyl methacrylate-co-methacrylic acid) hydrogel into a tissue-engineering scaffold with architectures driving heart tissue integration. The construct contains parallel channels to organize cardiomyocyte bundles, supported by micrometer-sized, spherical, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
486
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 596 publications
(516 citation statements)
references
References 41 publications
16
486
2
3
Order By: Relevance
“…In recent literature, higher ratios of M2/M1 macrophages concomitantly with an absence of a foreign body response have been found with scaffolds having 30-40-mm pores when compared to hosts with nonporous implants. 47 In this study, TiO 2 -HAP-GEL scaffolds had 34% porosity with 1.52 -0.8-mm pores and were not engineered in vitro as in other studies 48 reporting a M1 predominant immune response (to engineered in vitro matrices); therefore, we would expect to have no foreign body response and a predominant M2 macrophage activity. Moreover, human MAPCs were recently found safe for clinical trials for treatment of graftversus-host disease (ClinicalTrials.gov NCT00677859, NCT00677222).…”
Section: Discussionmentioning
confidence: 99%
“…In recent literature, higher ratios of M2/M1 macrophages concomitantly with an absence of a foreign body response have been found with scaffolds having 30-40-mm pores when compared to hosts with nonporous implants. 47 In this study, TiO 2 -HAP-GEL scaffolds had 34% porosity with 1.52 -0.8-mm pores and were not engineered in vitro as in other studies 48 reporting a M1 predominant immune response (to engineered in vitro matrices); therefore, we would expect to have no foreign body response and a predominant M2 macrophage activity. Moreover, human MAPCs were recently found safe for clinical trials for treatment of graftversus-host disease (ClinicalTrials.gov NCT00677859, NCT00677222).…”
Section: Discussionmentioning
confidence: 99%
“…This pore structure allowed us to accurately assess the effect of pore size on the FBR. We found that when the pores were 30-40 μm in diameter, there was considerable angiogenesis and much reduced capsule formation (loose, open collagen fibrils, in contrast to highly oriented, dense collagen) [24][25][26][27]. When pores were larger or smaller, the classic FBR was observed.…”
Section: The Future Of Biocompatibilitymentioning
confidence: 95%
“…The solid slab will heal with the classic FBR, a dense capsule surrounding the implant. The same polymer with 30-μm pores will show little or no fibrosis, excellent vascularization, and reconstruction of the original tissue [25]. We have in the two specimens described here the same biomaterial used in the same specific application.…”
Section: The Manifesto and A Biocompatibility Definition For The Twenmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, it was used a fi brin patch seeded with swine kDa and it can be crosslinked in the presence of calcium ions to form a gel structure and has recently been applied in myocardial tissue engineering, as an injectable cell delivery vehicle [48][49][50][51]. Due to its biocompatibility has been approved by FDA for human use as wound dressing material [52].…”
Section: Hyaluronic Acid (Ha)mentioning
confidence: 99%